Implementation of Heritage Building Conservation Policy (a Study on Kapitan Village in Palembang City) - Aliyyah Haruko Azhar Putri; Sriati; M.Husni Thamrin; Ahar (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Kapitan Village is part of the history of the formation of Chinese ethnic settlements in Palembang and was once used as the residence of the Kapitan and his family. Over time, the Kapitan's house has become a cultural heritage site that must be protected by the government. The Palembang City Government, particularly the Palembang Culture and Tourism Office, strives to preserve Cultural Heritage in Palembang through the Cultural Heritage Preservation Policy. Researchers used a qualitative descriptive method with a theoretical approach by Van Meter and Van Horn to obtain in-depth information related to the research objectives. Data collection techniques were carried out through interviews, observation, documentation, and literature review. The results of the study show that the implementation of the cultural heritage preservation policy in Kampung Kapitan, Palembang City, is quite effective. The standards and objectives of the policy have been implemented in accordance with Mayor Regulation No. 45 of 2020, although technical supervision still needs to be improved. Human resources and community participation were assessed as good, but coordination between agencies was not yet fully optimal. Social and political conditions supported preservation, while economic constraints were the main challenge. The attitude of the implementers showed a positive commitment to cultural preservation, although openness and cooperation between parties still needed to be strengthened so that policy implementation could be more sustainable.